Annotated record of Mn deposits from DOMES sites and chemical analysis of a Mn nodule from the Bermuda Rise - Ronald K Sorem; Ronald H Fewkes (PANGAEA, 1977)
It is the purpose of this chapter to present information available at the time of publication on the internal features of manganese nodules, to offer genetic interpretations of these features, and to suggest new lines of research. To judge from the limited data available on ocean floor crusts rich in manganese and iron (see, for example, Aumento et al., 1968, doi:10.1594/PANGAEA.862565 ), much of what is learnt about nodules may be applied eventually to an understanding of the origin of these more continuous masses. A genetic relationship between these two is likely.
Supplement to: Sorem, RK; Fewkes, RH (1977): Internal characteristics (Chapter 6). in: Glasby, G.P. (Ed.), Marine Manganese Deposits. Elsevier, Amsterdam, Netherlands, 147-183, https://store.pangaea.de/Projects/NOAA-MMS/Sorem-Fewkes_Ch6.pdf